Calophyllum inophyllum extract as a natural enhancer for improving physical properties of bioplastics and natural antimicrobial - Rini Umiyati; Ria Millati; Teguh Ariyanto; Chusnul Hidayat (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Umiyati R, Millati R, Ariyanto T, Hidayah C. 2020. Calophyllum inophyllum extracts as a natural enhancer for improving physical properties of bioplastics and antimicrobial activity. Biodiversitas 21: 3294-3302. The utilization of Calophyllum inophyllum (or nyamplung) cake (NC) is still limited, only as fertilizer and animal feed. This research aimed to evaluate C. inophyllum (or nyamplung) cake extract (NCE) and its utilization as an antimicrobial agent in packaging material. Bioplastics were prepared by the thermo-compression method. The results showed that the NC and NCE contained tannins and amide groups. They had antimicrobial activities toward Escherichia coli and Staphylococcus aureus. Only NCE had antifungal toward Aspergillus nigger. Therefore, HPS bioplastic containing NCE exhibited antibacterial. Besides, NCE and NC contained carbonyl and amide groups. As a result, NCE addition was able to significantly increase tensile strength (?) of bioplastic, in which it was about 1.5 times higher compared to control. But NCE did not have a significant effect on elongation at break (?) and modulus of elasticity (Y). Water solubility (WS) and water vapor permeability (WVP) were reduced with an increase in NCE concentration. HPS-NCE bioplastics show a finer and more homogeneous texture compared to control bioplastic. The NCE shows the ability as a natural enhancer for improving bioplastics properties as well as function as an antibacterial agent against Escherichia coli and Staphylococcus aureus bacteria in bioplastics.